2021
DOI: 10.1136/bmjopen-2020-047919
|View full text |Cite
|
Sign up to set email alerts
|

Top 10 (plus 1) research priorities for expectant families and those with children to age 24 months in Alberta, Canada: results from the Family Research Agenda Initiative Setting (FRAISE) priority setting partnership project

Abstract: ObjectiveThe study objective was to identify the top 10 research priorities for expectant parents and caregivers of children up to age 24 months.DesignA priority setting partnership using a modified James Lind Alliance approach was implemented. First, a core steering committee was formed, consisting of 17 parents, clinicians and community agency representatives. Second, through in-person collaboration with steering committee members, we developed and distributed a survey to identify research priorities across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Early interventions can also prevent the long-term consequences of parent mental illness from becoming imbedded in children’s biological and behavioral development (Bernard-Bonnin et al, 2004 ). Moreover, in a three-year patient-oriented research-priority setting initiative (Bright et al, 2018 ), parents of young children (from conception to age 2) identified their top priority as support for families to develop healthy coping and emotion regulation (Brockway et al, 2021 ). Families also wanted access to evidence-based information, tailored to their needs, delivered in timely formats (Brockway et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early interventions can also prevent the long-term consequences of parent mental illness from becoming imbedded in children’s biological and behavioral development (Bernard-Bonnin et al, 2004 ). Moreover, in a three-year patient-oriented research-priority setting initiative (Bright et al, 2018 ), parents of young children (from conception to age 2) identified their top priority as support for families to develop healthy coping and emotion regulation (Brockway et al, 2021 ). Families also wanted access to evidence-based information, tailored to their needs, delivered in timely formats (Brockway et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The BEAM App is broadly consistent with priority-setting research in parents of young children which highlights a desire for more support for families to develop healthy coping and emotion regulation (75). Parents have also indicated a need for access to evidence-based information, tailored to their needs, delivered in timely formats (75). Our team is committed to improving the BEAM program and are making multiple systematic improvements to all aspects based on pilot study results and ongoing input from the parent advisory board.…”
Section: Discussionmentioning
confidence: 67%
“…The acceptability findings and preliminary treatment effects for some of the mental health symptoms suggest that the Appbased BEAM program is promising intervention for addressing family mental health and parenting needs during the pandemic and its aftermath. The BEAM App is broadly consistent with priority-setting research in parents of young children which highlights a desire for more support for families to develop healthy coping and emotion regulation (75). Parents have also indicated a need for access to evidence-based information, tailored to their needs, delivered in timely formats (75).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our campaigns on Facebook and Instagram had substantial success in reaching knowledge users, 28,641 and 2,954 people respectively across both surveys. In a similarly Pan-Canadian PSP conducted by Brockway et al, most participants were recruited through social media campaigning (n=337, 70.2%), reflecting similar effectiveness as our initial survey dissemination, which collected responses from 330 unique respondents (12). While our PSP survey recruitment was strictly limited to social media-and electronic network-based promotions, Brockway et al integrated an in-person component where participants were informed of the study then provided with a device to record their responses (12).…”
Section: Content and Impact Of Individual Social Media Postsmentioning
confidence: 99%